Effect of Nanoclay Loading on Physical and Mechanical Properties of Epoxy Composites - B. Suresha* (International Journal of Advance in Molecular Engineering, 2026)
The effects of multilayer silicate loading on hardness, tensile, and impact properties were examined by developing epoxy–nanoclay composites with 0–5 wt% nanoclay. A desirable compromise between reduced void content and higher Shore D hardness was reached with an ideal nanoclay loading of 3 wt%, which reflected improved load transfer and increased matrix stiffness as a result of limited polymer chain mobility. Tensile strength and modulus rose up to 3 wt% nanoclay, aligning with micromechanical predictions from the Halpin–Tsai model for high aspect-ratio platelet reinforcements. Impact strength exhibited a 56% enhancement at 3 wt% due to synergistic fracture toughening mechanisms, including crack pinning, deflection, branching, and localized plastic shear, whereas a reduction at 5 wt% was ascribed to platelet tactoid aggregation and void-induced stress concentrations. The statistical study demonstrated that the 3 wt% composition shown markedly enhanced impact resistance. Overall, the findings show that mechanical reinforcement is maximized at an ideal nanoclay loading of 3 wt% before aggregation-driven embrittlement imposes declining returns.
Keywords: Epoxy-nanoclay composites; Hardness; Impact strength; tensile properties